Systemic proteasome inhibition induces sustained post-stroke neurological recovery and neuroprotection via mechanisms involving reversal of peripheral immunosuppression and preservation of blood-brain-barrier integrity - Doeppner, Thorsten Roland; Kaltwasser, Britta; Kuckelkorn, Ulrike; Henkelein, Petra; Bretschneider, Eva; Kılıç, Ertuğrul; Hermann, Dirk M. (Springer, 2016)
In view of its profound effect on cell survival and function, the modulation of the ubiquitin-proteasome-system has recently been shown to promote neurological recovery and brain remodeling after focal cerebral ischemia. Hitherto, local intracerebral delivery strategies were used, which can hardly be translated to human patients. We herein analyzed effects of systemic intraperitoneal delivery of the proteasome inhibitor BSc2118 on neurological recovery, brain injury, peripheral and cerebral immune responses, neurovascular integrity, as well as cerebral neurogenesis and angiogenesis in a mouse model of transient intraluminal middle cerebral artery occlusion. Systemic delivery of BSc2118 induced acute neuroprotection reflected by reduced infarct volume when delivered up to 9 h post-stroke. The latter was associated with reduced brain edema and stabilization of blood-brain-barrier integrity, albeit cerebral proteasome activity was only mildly reduced. Neuronal survival persisted in the post-acute stroke phase up to 28 days post-stroke and was associated with improved neurological recovery when the proteasome inhibitor was continuously delivered over 7 days. Systemic proteasome inhibition prevented stroke-induced acute leukocytosis in peripheral blood and reversed the subsequent immunosuppression, namely, the reduction of blood lymphocyte and granulocyte counts. On the contrary, post-ischemic brain inflammation, cerebral HIF-1 alpha abundance, cell proliferation, neurogenesis, and angiogenesis were not influenced by the proteasome inhibitor. The modulation of peripheral immune responses might thus represent an attractive target for the clinical translation of proteasome inhibitors.
WOS: 000387231300044
PubMed ID: 26572637
Keywords: Cerebral Ischemia; Stroke; Proteasome; Neuroprotection; Neuroregeneration; Inflammation